Soekarno's Rhetorical Style - Munawwir Hadiwijaya (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
This research looks at the rhetorical methods utilized by Soekarno, Indonesia's first president, at the "15th United Nations General Assembly on September 30, 1960, in New York." The goal of this research is to (1) determine which of Soekarno's speech methods he used., (2) the messages that he sends forth. To aid in data analysis, a descriptive qualitative design is used. The theories of Kenneth Burke and Aristotle are employed to comprehend and interpret the evidence. The precise information comes from Soekarno's speech, "To Build a New World." The data demonstrate that Soekarno employs both Burke's and Aristotle's beliefs. Soekarno employs the "pentad," which includes agent, scene, act, agency, and purpose, based on Burke's theory. Soekarno employs logical, emotional, and ethical appeals in accordance with Aristotle's theory.